The Effect of Perceived Usefulness, Perceived Ease of Use On Attitudes and Interest in Using Regional Financial Management Information Systems - Elly Asmara; Dwi Ratmono (Iapa Proceedings Conference, 2021)
The era of globalization is an advanced internet use one of the strategic measures for innovation, for it is this penelian circuitry following results Effect of Perceived Usefulness Of Attitude Toward Using ditermia, where the higher the user's perception of the benefits created by SIPKD it is increasingly having a good acceptance. Effect of Perceived Ease Of Use Of Attitude Toward Using, received Perceived ease of use makes one believe that computers are easy to understand and use and can be defined a person would believe that by using the system very easy to learn, easy to be done according to its desires and ease to operate. InfluenceAttitude Toward Using Against Behavioral Intention, has an effect where the more you have a good attitude of acceptance of SIPKD, the more you have an interest in using technology.